DASAR GENETIK OBESITAS VISERAL - Indra, Muhammad Rasjad (Jurnal Kedokteran Brawijaya, 2006)
Obesity is defined as an excess proportion of totalbody fat. Nearly 40 million adults in the United States can be defined as obese. There are several indexes used to assess  obesity. The most common measure of obesity is the body mass index (BMI). Obesity occurs when a person's calorieintake exceeds the amount of energy he or she burns. Obesity tends to run in families, suggesting that it may have a genetic cause. However, family members share not only genes but also diet and lifestyle habits that may contribute to obesity. Separating these lifestyle factors from genetic ones is often difficult. Still, growing evidence points to heredity as a strong determining factor of obesity. In one study of  adults who were adopted as children, researchers found that their subjects' adult weights were closer to their biological parents' weights than to their adoptive parents'. The environment provided by the adoptive family apparently had less influence on the development of obesity than the person's genetic makeup. Although genes are an important factor in many cases of obesity, a person's environment also plays a significant part. Psychological factors may also influence eating habits. Many people eat in response to negative emotions such as boredom, sadness, or anger. Key words:Genetic, Obesity, visceral